Risk Sharing Opportunities and Macroeconomic Factors in Latin American and Caribbean Countries : A Consumption Insurance Assessment - Ventura, Luigi (World Bank, Washington, DC, 2012)
This paper evaluates the degree of consumption insurance enjoyed by Latin American and Caribbean countries, with respect to various reference areas, by estimating a parameter expressing the sensitivity of a country's consumption growth to a measure of idiosyncratic shocks to income. The paper surveys common econometric implementations of "consumption insurance tests." The author proposes some econometric procedures in order to detect the actual presence of international risk sharing, as well as to assess the relative impact of idiosyncratic versus aggregate shocks. The evidence suggests that Latin American and Caribbean economies have been hit by non-diversifiable income shocks, that idiosyncratic risk is relatively more important than aggregate risk, and that some countries in the region appear to enjoy a certain amount of international risk diversification. The paper also identifies some macroeconomic factors that may be responsible for a higher or lower degree of risk pooling (such as international openness, financial depth, and credit availability). The findings show that the financial development of an economy is a crucial factor in determining the amount of risk sharing opportunities, as well as public expenditure. The preliminary results also suggest that trade openness and shocks to terms of trade play an important role in determining the degree of insurability of such risks.